PENGGUNAAN KOEFISIEN ALFA DALAM PERHITUNGAN UPAH MINIMUM DAN AKIBATNYA TERHADAP DESENTRALISASI FISKAL SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Widyatama, Denta Putra; Indrawati; Ramli, Lanny; Ananta, Ahmad Rizal Roby; Zita, Alena (Jurnal Ketenagakerjaan, 2025)
Wages are one of the important issues in Labor Law, particularly from the workers' perspective. The enactment of Law No. 11 of 2020 concerning Job Creation in Indonesia, which was later revoked by Law No. 6 of 2023, introduced substantial changes to the structure of Labor Law, specifically in the existence of Alpha Coefficient as a substitute for KHL. This Alpha Coefficient is replacing the KHL and representing functions as an economic index sector variables in Indonesia. This study aims to examine two main issues: first, the legal and conceptual implications of replacing KHL with the Alpha Coefficient in calculating minimum wages; and second, the effect of this change on the authority and role of the Regional Wage Council as part of Indonesia’s fiscal decentralization policy. The research employs a statutory and conceptual approach supported by a review of the development of the national wage system. The findings indicate that the existence of the Alpha Coefficient enhances legal certainty by establishing a definitive parameter in wage calculations, thereby improving workers’ welfare protection. Furthermore, the Regional Wage Council’s position is strengthened through the restoration of tripartite negotiations, ensuring a more balanced and decentralized fiscal and also wage-setting mechanism. The Alpha Coefficient significantly increase the workers wealth by, following the main rights on Indonesian Constitution.